Characteristics of Carbonaceous Species of PM2.5 in Chiang Mai City, Thailand - Sawaeng Kawichai; Tippawan Prapamontol; Fang Cao; Wenhuai Song; Yan-Lin Zhang (Aerosol and Air Quality Research)
Abstract Over the past decade, biomass burning has significantly elevated PM2.5 levels in upper northern Thailand. However, studies of source contributions from carbonaceous aerosols are limited in upper northern Thailand. Therefore, this study aimed to investigate the concentrations and characteristics of carbonaceous in PM2.5; and estimate their source contributions. The PM2.5 samples were collected from January to May 2017 in Chiang Mai City, located in Chiang Mai Province, Thailand. The mean concentrations ± S.D. of PM2.5, organic carbon (OC), elemental carbon (EC), and water-soluble organic carbon (WSOC) were 38.7 ± 18.2, 10.0 ± 4.89, 1.35 ± 0.68, and 7.61 ± 4.08 µg m−3, respectively. The OC/EC ratio ranged from 2.03 to 12.9, with a mean of 7.71 ± 0.15. The study demonstrated a WSOC/OC ratio of 0.75 ± 0.15, indicating that the WSOC was significantly contributed by biomass burning. The high level of primary organic carbon (POC) in the total organic carbon (TOC) found in this study confirms that biomass burning was the dominant source of OC in this season. The secondary organic carbon (SOC) contributions of 39.5% of TOC suggest a higher prevalence of air pollution and its role in encouraging the condensation or adsorption of volatile organic compounds (VOCs). Therefore, this finding indicates that the concentrations of carbonaceous aerosol pollution in Chiang Mai City are of significant concern.